2017
DOI: 10.1590/0103-6440201600953
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Particles in Two-Dimensional and Three-Dimensional Osteogenic Cell Cultures

Abstract: This study aimed to investigate the influence of a three-dimensional cell culture model and bioactive glass (BG) particles on the expression of osteoblastic phenotypes in rat calvaria osteogenic cells culture. Cells were seeded on two-dimensional (2D) and threedimensional (3D) collagen with BG particles for up to 14 days. Cell viability and alkaline phosphatase (ALP) activity was performed. Cell morphology and immunolabeling of noncollagenous bone matrix proteins were assessed by epifluorescence and confocal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…So it could be concluded that the stereochemistry of the polymers used for coating glasses greatly influence the cell growth and survival. This agrees with another study [13] and could be explained by the organization and maturation of the extracellular matrix surrounding cells by the created threedimensional system. An additional approach for the detection of cells viability is the determination of LDH levels.…”
Section: Discussionsupporting
confidence: 93%
“…So it could be concluded that the stereochemistry of the polymers used for coating glasses greatly influence the cell growth and survival. This agrees with another study [13] and could be explained by the organization and maturation of the extracellular matrix surrounding cells by the created threedimensional system. An additional approach for the detection of cells viability is the determination of LDH levels.…”
Section: Discussionsupporting
confidence: 93%
“…The new bone formed into the cavity increased approximately 25%, 50%, and 55%, respectively, with 4, 7, and 11 sessions of LT and compared to referential Control values obtained in IBB-filled but not irradiated with lowlevel laser, i.e., combining the use of IBB with seven sessions of LT seems to be an optimal approach to greatly improve the recovery of calvarial defects. It would be important to verify if the optimal effects of seven sessions of LT on bone mineralization are also observed in cavities filled with other biomaterials such as the bioactive glass particles which have been used in in vitro studies from other investigators (Alves et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Resident osteoblasts potentially clustered quicker in the stiff matrix than soft matrix, due to increased cellular and matrix density. We characterised this 3D bone stroma extensively, and did not limit the study to mineralisation assessments via ALP assay or alizarin red staining 34 . The alizarin red stain or von Kossa stain indicated mineralisation (dystrophic calcification) 65 .…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to undertake extensive characterisation of 3D in vitro bone nodule formation in dense collagen matrices, to match, at a minimum, that done for 2D bone nodule formation, including mineralisation and gene markers. For confirmation of definitive in vitro bone nodule formation it was paramount to measure structure and composition as well as to investigate of specific gene panels for all stages of bone formation 34 36 .…”
Section: Introductionmentioning
confidence: 99%